2022
DOI: 10.3390/toxins14110758
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone Induces Apoptosis in Porcine Endometrial Stromal Cells through JNK Signaling Pathway Based on Endoplasmic Reticulum Stress

Abstract: Zearalenone (ZEA) is an estrogen-like mycotoxin characterized mainly by reproductive toxicity, to which pigs are particularly sensitive. The aim of this study was to investigate the molecular mechanism of ZEA-induced apoptosis in porcine endometrial stromal cells (ESCs) by activating the JNK signaling pathway through endoplasmic reticulum stress (ERS). In this study, ESCs were exposed to ZEA, with the ERS inhibitor sodium 4-Phenylbutyrate (4-PBA) as a reference. The results showed that ZEA could damage cell st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In SiHa cells, Trichomonas vaginalis triggers ERS-induced mitochondrial apoptosis through the IRE1/ASK1/JNK/ Bcl-2 family protein pathways [ 39 ]. Our previous research indicates that adding 4-PBA can alleviate toxic damage and apoptosis in porcine germ cells and alleviate ERS caused by ZEA [ 14 , 40 ]. Bcl-2 family proteins play a critical role in regulating the release of apoptotic factors related to mitochondria, which are mainly divided into pro-apoptotic factors and anti-apoptotic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In SiHa cells, Trichomonas vaginalis triggers ERS-induced mitochondrial apoptosis through the IRE1/ASK1/JNK/ Bcl-2 family protein pathways [ 39 ]. Our previous research indicates that adding 4-PBA can alleviate toxic damage and apoptosis in porcine germ cells and alleviate ERS caused by ZEA [ 14 , 40 ]. Bcl-2 family proteins play a critical role in regulating the release of apoptotic factors related to mitochondria, which are mainly divided into pro-apoptotic factors and anti-apoptotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The cell viability was observed using a fluorescence optical microscope. Further details can be found in a previous study conducted by our laboratory [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At high concentrations, ZEA causes mitochondrial dysfunction, EnR stress, apoptosis, and autophagy. ZEA reduces the protein expression of Nrf2 and HO‐1 to further induce oxidative stress and cause cell apoptosis via the p38, JNK, and ERK MAPK pathways 63 , 64 , 65 . Bai et al found that ZEA can induce apoptosis by modulating EnR stress though the PERK and ATF6 signaling pathways in porcine trophectoderm cells 66 .…”
Section: Main Fusarium Mycotoxinsmentioning
confidence: 99%
“…The cells were collected and subjected to FACS Calibur flow cytometry (BD, Franklin Lakes, NJ, USA) to detect their Ca 2+ fluorescence intensity. For the details, see our laboratory's previous study [32].…”
Section: Determination Of Ca 2+mentioning
confidence: 99%